Memórias alimentares dos moradores do município de Beberibe – Ceará: um relato sobre o manifesto cultural alimentar - Santos, Paulo Henrique Ribeiro dos (2018)
Food is the main factor for the determination and firmness of the culture of a people or of an entire society, because it will define the food behavior of this population through geography, that is, nature plays the role of mapping the food and how it whether through the biome or even in the influences of other peoples in the cultural exchange through immigration. For the elaboration of this work, it was used through oral history and ethnography the application of interviews with the intention of mapping the food culture of the residents of Beberibe, defining the points of interviews of the municipality. The importance of this research is to map and analyze the daily diet of the drinkers, in order to compare food from the old to the present, and how religion and popular feasts can influence the food of the residents.